Hommage to Pierre Villard - . (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
Pierre Villard, who was part of the scientific committee of this journal since its foundation in 2017, has left to join the Assyrian kings he loved so much. As director of the journal I would have liked to pay him a worthy tribute. But as his wife I cannot. His obituary will appear in the second issue of the journal. Think of him